The Qur'an's reformation of Judaism and Christianity: return to the origins - Zellentin, Holger Michael (Routledge Studies in the Qur'an Ser., 2019)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Notes on contributors -- 1 The Qur'an and the reformation of Judaism and Christianity -- Part I The Qur'an, the Bible, and the Islamic tradition -- 2 What would Ibn Taymiyyah make of intertextual study of the Qur'an? The challenge of the isrāʾīliyyāt -- 3 Prophecy and writing in the Qur'an, or why Muhammad was not a scribe -- 4 A "Religious Transformation in Late Antiquity": Qur'anic refigurations of pagan-Arab ideals based on biblical models -- 5 Meccan Gods, Jesus' divinity: an analysis of Q 43 Sūrat al-Zukhruf -- Part II The Qur'an and the Bible -- 6 Gentile purity law from the Bible to the Qur'an: the case of sexual purity and illicit intercourse -- 7 David and Solomon: antecedents, modalities, and consequences of their twinship in the Qur'an -- Part III The Qur'an and Judaism -- 8 Pharaoh's submission to God in the Qur'an and in rabbinic literature: a case study in Qur'anic intertextuality -- 9 The eschatological counter-discourse in the Qur'an and in the Babylonian Talmud, Sanhedrin 90b-91a -- Part IV The Qur'an and Christianity -- 10 Thrice upon a time: Abraham's guests and the study of intra-Qur'anic parallels -- 11 "Killing the prophets and stoning the messengers": two themes in the Qur'an and their background -- 12 On the Qur'an and Christian heresies -- 13 Reflections on the Qur'an, Christianity, and intertextuality -- Index of Qur'anic references -- Index.